2017
DOI: 10.1590/0103-8478cr20151582
|View full text |Cite|
|
Sign up to set email alerts
|

Physiological quality of dual-purpose wheat seeds from plants subjected to artificial defoliation

Abstract: Defoliation may play a role in source-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…Taken together, the results indicate sensitivity in the reproductive stage of wheat plants to define seed vigor due light restriction. Similar to results obtained by Rodolfo et al (2017), who found no effects on the germination of the seeds produced, but there was a reduction in vigor, probably due to the lower content of carbohydrates (starch) in the seeds, by limiting the source-sink relationship of wheat plants, manipulating the source factor through defoliation between the tillering and booting stages. Thus, in the stages that precede the anthesis, the formation of floral structures occurs (Marcos Filho, 2015), later double fertilization, that is, the union of the nuclei spermatic (n) with the oosphere (n) and the polar nuclei (2n), to then start cell division, growth of the zygote (2n) and the reserve tissue, the endosperm (3n) (Berger, 2003).…”
Section: /8supporting
confidence: 86%
See 1 more Smart Citation
“…Taken together, the results indicate sensitivity in the reproductive stage of wheat plants to define seed vigor due light restriction. Similar to results obtained by Rodolfo et al (2017), who found no effects on the germination of the seeds produced, but there was a reduction in vigor, probably due to the lower content of carbohydrates (starch) in the seeds, by limiting the source-sink relationship of wheat plants, manipulating the source factor through defoliation between the tillering and booting stages. Thus, in the stages that precede the anthesis, the formation of floral structures occurs (Marcos Filho, 2015), later double fertilization, that is, the union of the nuclei spermatic (n) with the oosphere (n) and the polar nuclei (2n), to then start cell division, growth of the zygote (2n) and the reserve tissue, the endosperm (3n) (Berger, 2003).…”
Section: /8supporting
confidence: 86%
“…However, the less vigorous lots reached a minimum of 93% in the AA. More intense reductions in seed vigor by the AA test were observed for wheat cultivars BRS Umbu and BRS Tarumã when submitted to defoliation, in which the minimum percentage in AA was 46% and 49%, respectively (Rodolfo et al, 2017), due to greater photosynthetic limitation.…”
Section: /8mentioning
confidence: 89%
“…Similarly, germination also has favorable results when defoliation on the plant is performed during tillering, that is, at the beginning of the vegetative period, as the restriction of sugars in this period does not alter the seeds' formation. (RODOLFO et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Dual-purpose wheat genotypes show high phytomass yield, a long vegetative phase, tolerance to trampling, high tillering potential and fast establishment, as well as forage and grain production (Martin et al, 2010;Szareski et al, 2016a;Carvalho et al, 2016a). This type of wheat is grown in several countries, including the United States of America, Uruguay and Argentina (Fontaneli, 2007;Hastenpflug, 2009;Kavalco et al, 2017). Research shows bromatological characteristics with crude protein around 27% and 69% total digestible nutrients (Hastenpflug et al, 2011;Carvalho et al, 2016b;Silveira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%